A systematic assessment of statistics, risk factors, and underlying features involved in pancreatic cancer - Aier, Imlimaong; Semwal, Rahul; Sharma, Anju; Varadwaj, Pritish Kumar (Cancer epidemiology, 2019)
•Pancreatic cancer has one of the lowest survival rates.•Early detection is almost impossible; late diagnosis is difficult to treat because of chemotherapy resistance.•Mutation of KRAS is not the only key driver for pancreatic cancer.•Best outcome may be through implementation of combination drug therapy. Pancreatic cancer remains the fourth leading cause of cancer-related death in the world, and will continue to become the number two cause of cancer-related death unless a remarkable breakthrough is achieved. With a slim chance of early diagnosis, surgery can only provide a median survival of 17–23 months. The presence of a dense stroma makes this cancer resilient to chemotherapy, with very few potent inhibitors like nab paclitaxelin available that can work in combination with chemotherapeutic agents. Survival rates, on the one hand, lie at 8.5%. Variation in types of pancreatic cancer, on the other hand, makes it notoriously difficult to come up with a practical solution for the treatment of this disease. A deeper understanding of the root cause would be beneficial for diagnosis. Advancement in the field of genomics has made the identification of novel biomarkers relatively easier. By coupling this factor with the production of suitable inhibitors, testing in large numbers can be made possible with the help of cell lines. With the combined efforts of biological knowledge and modern technology, the cure for pancreatic cancer could be at hand.